Charge Transfer Reactions in CO2 Electroreduction on Manganese Doped Ceria. Issue 6 (15th January 2019) - Huang, Zhidong; Shang, Lei; Qi, Huiying; Zhao, Zhe; Tu, Baofeng; Yang, Weishen; Cheng, Mojie
Abstract: The key to electrochemical conversion of carbon dioxide (CO2 ) into fuels lies in effient charge transfer reactions. Here, we depict from the polarzation resistance analysis that the electroreduction of CO2 to CO on manganese doped ceria (CMO) passes through two elementary charge transfer reactions. One reaction is asscociated with ( C O 3 ) O, S to ( C O 3 ) O, S and another associated with ( C O 3 ) O, S to CO. As the rate determing step, the first one has an apparenent acitvation energy of 178.7 kJ mol −1 and a pressure dependence of P C O 2 0 . 76 P C O 0 . 24 . The second one has an apparent acitvation energy of 100.6 kJ mol −1 and a pressure dependence of P C O 2 0 . 27 P C O 0 . 73 . Based on the experimental results, we give the kenetic expression for the CO2 electroreduction rate on CMO. Abstract : Charge transfer reactions are investigated for high temperature carbon dioxide electroreduction on manganese doped ceria. The second electron transfer step is determined as the key step.